High prevalence of arterial hypertension in a Brazilian Northeast population of low education and income level, and its association with obesity and metabolic syndrome - Lyra,Rüy (2012)
OBJECTIVE: The objectives of this study are to estimate the prevalence of arterial hypertension (AH) in an adult population with a predominance of families with low education and income levels, in the hinterlands of Pernambuco, Brazil, and to analyze its association with other factors related to cardiovascular diseases (CVD). METHODS: A cross-sectional study in 2008/2009 was conducted with a sample of 198 subjects stratified by age, and representative of the urban adult population of the Canaã district of city of Triunfo, in the hinterlands of Pernambuco, Brazil. RESULTS: One hundred ninety eight individuals with average age of 57.7 years old (31 to 90 years-old), mainly women (65.6%), and with low income and education levels (81.3% with a monthly income of less than one minimum wage) were evaluated. Among these, 127 (64.1%) were identified as having AH, 54 (42.5%) of whom had no prior diagnosis. From those who were previously diagnosed, only 31.3% had good blood pressure control. Higher prevalence was observed in those individuals with lower incomes, higher body mass indexes (BMI), and those with metabolic syndrome (MS). CONCLUSION: These data demonstrated that there was a high prevalence of AH in the urban, low education and income levels adult population of Triunfo, strongly associated with lower income levels, elevated BMI, and the presence of MS; and a high prevalence of bad blood pressure control among the previously diagnosed cases. These results indicate that more effective interventions for early detection and adequate control of this disease and its comorbidities are necessary.